2004
DOI: 10.14411/fp.2004.014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the knowledge of amphizoic amoebae infecting fish

Abstract: Abstract. Free-living amoebae infecting freshwater and marine fish include those described thus far as agents of fish diseases, associated with other disease conditions and isolated from organs of asymptomatic fish. This survey is based on information from the literature as well as on our own data on strains isolated from freshwater and marine fish. Evidence is provided for diverse fish-infecting amphizoic amoebae. Recent progress in the understanding of the biology of Neoparamoeba spp., agents responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 84 publications
1
44
0
Order By: Relevance
“…However, recent research on AGD has suggested that some cultured strains of Neoparamoeba sp. isolated from AGD infected fish gills are not bacterivorous (Dyková & Lom 2004). Despite this, during the present study the fish inoculated with Winogradskyella sp.…”
Section: Discussionmentioning
confidence: 67%
“…However, recent research on AGD has suggested that some cultured strains of Neoparamoeba sp. isolated from AGD infected fish gills are not bacterivorous (Dyková & Lom 2004). Despite this, during the present study the fish inoculated with Winogradskyella sp.…”
Section: Discussionmentioning
confidence: 67%
“…Six of them were subjected to sequence and riboprinting analyses of SSU rRNA genes (Dyková et al 2001, Dyková andLom, 2004). Phylogenetic analyses resulted in identification of one strain from the brain of a fish with Naegleria australiensis and another five strains as closely related to N. clarki.…”
Section: Fish-isolated Naegleria Strains and Their Phylogeny Inferredmentioning
confidence: 99%
“…Subsequently, other amoebae species have been implicated in gill disease including Thecamoeba hoffmani in rainbow trout Oncorhynchus mykiss, Neoparamoeba pemaquidensis in Atlantic salmon Salmo salar, Platyamoeba sp. in turbot Scophthalmus maximus, and other unidentified amoebae in Atlantic salmon and rainbow trout (Leiro et al 1998, Bermingham & Mulcahy 2004, Dyková & Lom 2004, Buchmann et al 2004.…”
Section: Introductionmentioning
confidence: 99%